Development of Canva Application Learning Media Increase Learning Outcomes Class X Economic Studies at SMAN 3 Bangkalan - Amiro Amiro; Ika Lis Mariatun; Yusrianto Sholeh (Journal of Educational Sciences, 2023)
This research is research into the development of learning media products using the Canva application for economics subjects for class X students at SMAN 3 Bangkalan. This research aims to (1) develop interactive learning media in economics subjects for students of SMAN 3 Bangkalan. (2) determine the feasibility of interactive learning media for economics subjects for students at SMAN 3 Bangkalan which is being developed. (3) Knowing the use of learning media using the Canva application can improve the learning outcomes of class X students at SMAN 3 Bangkalan. This development research is carried out using R&D (research and development) which consists of potential and problems, information gathering, product design, design validation, design improvement, product testing, product revision, use testing, product revision, and product manufacturing. Based on this research, for the assessment, material experts obtained a percentage score of 78% in the (worthy) category, media experts obtained a percentage of 83.3% in the (very worthy) category, field practitioners obtained a percentage of 98% in the (very worthy) category. category (very worthy). category (very worthy), and improve learning outcomes with a score of 0.82 or 82% in the category (high). Based on the pretest posttest student learning outcomes were initially 60-70, after using learning media using the Canva application it became 90-95, increasing from 15-30.